(untitled) (Tribhuvan University Journal of Microbiology, 2018)
Objectives: This study aimed to identify the microbiological profile of various catheter tips, and multidrug resistance pattern of extended spectrum β-lactamase (ESBL) producing E. coli and Klebsiella spp. isolates. Methods: A descriptive analysis of 263 catheter tip specimens processed for culture and antimicrobial susceptibility testing was carried out in B&B Hospital, Lalitpur. Five different types of catheter tips were analyzed for microbiological growth and antimicrobial susceptibility testing. Results: Among catheter tips, the highest percentage of microbial growth was observed in tracheostomy tip. Monomicrobial growth was recorded in 82.9% catheter tips and polymicrobial growth was observed in 17.1% tip samples. Of 180 isolates, gram negative rods (76.6%) followed by yeast (19.4%) and gram-positive cocci (3.9%) were isolated. Gram negative Acinetobacter spp. (25%) and Pseudomonas spp. (23.3%) and gram-positive Enterococcus spp. (2.2%) were the most frequently isolated bacteria. However, carbapenam was the most effective antibiotic for both groups. Conclusion: Of the total isolates tested, 61.4% were found to be multidrug resistant (MDR). Among gram negative rods, 22.2% E. coli and 27.3% Klebsiella spp. were confirmed as ESBL producer. It is recommended to apply standard protocol during insertion and removal of catheter which may help in managing nosocomial infection associated with catheters.